Natural biomolecules and derivatives as anticancer immunomodulatory agents - Bernitsa, Stavroula; Dayan, Rotem; Stephanou, Anastasis; Tzvetanova, Iva D.; Patrikios, Ioannis S. (Frontiers in Immunology, 2023)
Despite advancements in chemotherapy, the issue of resistance and non-responsiveness to many chemotherapeutic drugs that are currently in clinical use still remains. Recently, cancer immunotherapy has gathered attention as a novel treatment against select cancers. Immunomodulation is also emerging as an effective strategy to improve efficacy. Natural phytochemicals, with known anticancer properties, been reported to mediate their effects by modulating both traditional cancer pathways and immunity. The mechanism of phytochemical mediated-immunomodulatory activity may be attributed to the remodeling of the tumor immunosuppressive microenvironment and the sensitization of the immune system. This allows for improved recognition and targeting of cancer cells by the immune system and synergy with chemotherapeutics. In this review, we will discuss several well-known plant-derived biomolecules and examine their potential as immunomodulators, and therefore, as novel immunotherapies for cancer treatment.